The Role of Involvement in the formation of Attitude and Purchase Intention on Brand's Social Media (Case Study: TikTok) - Shahril Shahputra Azis; Triana Rahajeng Hadiprawoto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Interactivity defines as the medium ability to provide synchronous communication by emphasizing the speed of response and quality of information. Previous research has examined the role of interactivity in enhancing customer's engagement and involvement towards mobile retail advertising. Moreover, brand familiarity and information quality are also factors that can increase involvement on social media based on the results of other studies that have been conducted in the context of social media. Furthermore, involvement is proven to be one of the factors that leverage the formation of positive attitude. As the result, purchase intention will be strengthened due to positive attitude towards a brand. This study aims to investigate the role of interactivity as one of the supporting predictors in increasing customer involvement in the context of social media. Data were collected from 195 Indonesian respondents who are classified as an active TikTok users with an age range of 18-48 years. Respondents were selected using predetermined sample criteria based on recommendations from previous studies. The results show that interactivity can positively shape involvement on a brand's social media. While other factors such as information quality and brand familiarity play a more dominant role in shaping customer involvement. Additionally, social media involvement positively influences attitude which leads to a higher intention to purchase. However, involvement was not proven to be one of the factors that escalate purchase intention.